Cutaneous Myiasis Caused by Tumbu Fly Larvae Infestation in an Infant: A Case Report - Amaewhule, O; Otaigbe, Be; Oyegbemi, Fa (International Journal of Infection Prevention, 2022)
Myiasis is a parasitic infestation of the body of a mammal caused by Cordylobia Anthropophaga (Tumbu fly) larvae. The infestation is prevalent in Sub-Saharan Africa, South-East Mexico and Central America. It is usually seen among rural dwellers and has no age or sex predilection. We report a case of Tumbu fly myiasis seen in a 7month-old male living in Port Harcourt, Nigeria who was erroneously thought to have bullous impetigo.
Keywords: Myiasis; infestation; mammal